Effect of sedimentary and metamorphic aggregate on static modulus of elasticity of high-strength concrete (2011)
Taking into account the increasing use of high-strength concrete as a structural material in Colombia, this paper shows the results of research carried out to investigate the effect of different types of coarse aggregate on the static elastic modulus, the compressive strength, the concrete density, and the pulse velocity. To do this, concrete mixes were cast using three different water binder ratios (w/c) (0.36, 0.32, and 0.28). Ordinary Portland cement and pulverized silica fume (SF) were used as cementitiuos materials, while four types of coarse aggregates obtained from different sources near Bogota, Colombia were utilized to prepare the concrete samples. Results were analyzed statistically and these showed that the behavior of all the tests followed a normal frequency distribution. Correlations were found among the mixes. From the experimental data obtained in this study, it was concluded that the equations proposed in standard codes overestimated the modulus of elasticity of high-strength concrete, so empirical equations were obtained in order to predict the elastic modulus of elasticity in high-strength concrete.